Biochronostratigraphy and paleoenvironment analysis of Neogene deposits from the Pelotas Basin (well 2-TG-96-RS), Southernmost Brazil - SILVA,WAGNER G. (2015)
This paper presents the integration of micropaleontological (palynology and foraminifera) and isotopic (87Sr/86Sr) analysis of a selected interval from the well 2-TG-96-RS, drilled on the onshore portion of the Pelotas Basin, Rio Grande do Sul, Brazil. A total of eight samples of the section between 140.20 and 73.50 m in depth was selected for palynological analysis, revealing diversified and abundant palynomorph associations. Species of spores, pollen grains and dinoflagellate cysts are the most common palynomorphs found. Planktic and benthic calcareous foraminifera were recovered from the lowest two levels of the section (140.20 and 134.30 m). Based on the stratigraphic range of the species of dinoflagellate cysts and sporomorphs, a span age from Late Miocene to Early Pliocene is assigned. The relative age obtained from the 87Sr/86Sr ratio in shells of calcareous foraminifers indicates a Late Miocene (Messinian) correspondence, corroborating the biostratigraphic positioning performed with palynomorphs. Paleoenvironmental interpretations based on the quantitative distribution of organic components (palynomorphs, phytoclasts and amorphous organic matter) throughout the section and on foraminiferal associations indicate a shallow marine depositional environment for the section. Two palynologicals intervals were recognized based on palynofacies analysis, related to middle to outer shelf (140.20 to 128.90 m) and inner shelf (115.75 to 73.50 m) conditions.